O processo de alfabetização com crianças do ensino fundamental mediado pela lousa digital interativa - Oliveira, Advanusia Santos Silva de (2018)
The process of literacy comprehends the intellectual, social, psychic, and emotional factors of the students, leading them to the experience of reading and writing in social practices. This research, entitled "The process of literacy with elementary school children mediated by the Interactive Whiteboard", is epistemologically established in the field of Education, grounded in the Piagetian and Ferreirian propositions of the psychogenesis of written language mediated by the Interactive Whiteboard (LDI) in the construction of different theoretical knowledge and practical propositions of doing, in the light of the interactionist theory of Vygotsky. In order to delineate a line of reasoning, the following research problem was chosen: how can the Interactive Whiteboard be able to provide literacy practices for primary school children through its use in teaching-learning processes? The general objective of the research is to investigate how the LDI can enable children's literacy practices in primary education 1 through its use in teaching-learning processes. In order to achieve the stated objective, the specific objectives were defined: identify in the pilot education plan of the 2nd year of primary education 1, actions that contribute to the literacy process mediated by the LDI; to verify how the LDI mediation can enhance the literacy process and analyze the application of the activities proposed in the pilot education plan. The theoretical basis was based on the publications that approach the conceptual and practical aspects of the research topic, considering its scope, with emphasis on the references involving Digital Information and Communication Technologies (TDIC); Interactive Whiteboard (LDI); Literacy and Teaching-Learning Process. The methodological approach chosen is the qualitative research, founded on the Bogdan and Biklen (1994) conjectures, based on the Participant Research of Brandão and Streck (2006), grounded on technical procedures, bibliographical, documentary and field study, exploratory and descriptive of Gil (2010). The following instruments were used for the the data collection: questionnaire of Lüdke and André (1986); participant observation of Lakatos and Marconi (2010); field diary of Macedo (2010) and Bogdan and Biklen (1994). The information collected was analyzed through content analysis (BARDIN, 2011), from which emerged four main categories: the cybercultural profile of 2nd year students B; the educational potential of LDI in the literacy of those surveyed; the LDI as a tactic for the development of language structure and cognitive aspects in the acquisition of literacy. The results show that: (a) the students are digital natives (they can be considered digital sages, by Prensk's (2009) observations), they are protagonists in individual or group practical activities and with excellent interaction between them; (b) the use of LDI in the teaching-learning process contributed to the learning and improvement of student literacy; (c) the interactions of the LDI in the applications of the activities allowed the enrichment of the language structure, configuring itself as one more resource to enhance the communication and the cognitive aspects of the students within the pedagogical practice.